2020
DOI: 10.3390/jcm9061876
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character Profile and Its Clinical Correlates in Male Patients with Dual Schizophrenia

Abstract: Personality traits are relevant in understanding substance use disorders (SUD) and schizophrenia (SZ), but few works have also included patients with dual schizophrenia (SZ+) and personality traits. We explored personality profile in a sample of 165 male patients under treatment, using the Temperament and Character Inventory-Revised. The participants were assigned to three groups of 55 patients each, according to previous diagnosis: SUD, SZ- and SZ+ (without/with SUD). We analyzed their clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
(111 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, considering personality by applying the BFQ-NA questionnaire, our study showed that low scores for conscientiousness, agreeableness, and openness predicted the risk of a DD and the onset of PUVG. In line with our results, the personality domains most often related to DDs in the literature are low conscientiousness and agreeableness, although, unlike our findings, no relationship with openness was found in previous work [ 36 , 37 ]. The same occurred for PUVG and GD [ 38 , 39 ], which was also associated with both low levels of conscientiousness and agreeableness and with male gender [ 40 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, considering personality by applying the BFQ-NA questionnaire, our study showed that low scores for conscientiousness, agreeableness, and openness predicted the risk of a DD and the onset of PUVG. In line with our results, the personality domains most often related to DDs in the literature are low conscientiousness and agreeableness, although, unlike our findings, no relationship with openness was found in previous work [ 36 , 37 ]. The same occurred for PUVG and GD [ 38 , 39 ], which was also associated with both low levels of conscientiousness and agreeableness and with male gender [ 40 ].…”
Section: Discussionsupporting
confidence: 89%
“…Focusing on conscientiousness, previous studies emphasized that this factor is not only lower in substance addicts but also in those with behavioural addictions, such as Internet use, gambling [ 41 ], and GD [ 42 ]. This would imply that these individuals have difficulty in complying with rules, lack autonomy, show less harm avoidance behaviour, tend to project blame onto third parties, and demonstrate disorder and imprecision, which would all act as an ideal combination for cultivating the start of a DD [ 36 ]. In terms of agreeableness, participants with a DD showed a greater tendency toward independence, a lower degree of social cooperation, and poor sensitivity to social stimuli [ 37 ], which are factors that would make outpatient follow-up difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Cloninger’s model can explain individual personality from two domains: temperaments that are relatively stable across the life span [ 97 ] and characters that are changeable to affect the environment and interaction with others through life [ 98 ]. Therefore, the model helps to explain the relationships between individual personality and physiological phenomena and psychiatric disorders from these two domains or specific profiles that consist of these factors robustly [ 99 , 100 ]. Although the use of the scales in this study might have enabled clearer explanations, these scales consist of more than 100 items, and researchers are worried that this would be a burden on participants who were just caring for COVID-19 patients.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Two other empirical studies explored the existence of indicators of easy clinical evaluation in high prevalence comorbidities such as schizophrenia and post-traumatic stress. Río-Martinez et al [ 10 ] have shown an endophenotype of personality traits characteristic of dual schizophrenia, which is related to more problematic clinical characteristics. The personality traits are modifiable and their consideration may be useful for designing specific intervention strategies.…”
mentioning
confidence: 99%